2009
DOI: 10.1348/096317909x471013
|View full text |Cite
|
Sign up to set email alerts
|

Proactive career behaviours and career success during the early career

Abstract: Hypothesis 3: The level of career planning at graduation will be positively associated with the level of career planning during early career. Proactive career behaviours 765Hypothesis 4: The level of networking behaviours at graduation will be positively associated with the level of networking behaviours during early career.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(90 citation statements)
references
References 46 publications
2
75
0
13
Order By: Relevance
“…Past research has already shown that many people experience shocks and that they impact their long-term career outcomes Scott & Hatalla, 1990;Williams et al, 1998), yet specific knowledge on whether and how the frequency of occurrence might impact career outcomes is less clear. For example, it would be interesting to examine whether experiencing multiple career shocks over time might diminish (negative shocks) or enhance (positive shocks) individuals' employability (Forrier et al, 2015), proactive career behaviours (De Vos et al, 2009) and the sustainability of their careers (De Vos & Van der Heijden, 2015). As such, we also call for research that examines the interplay between career shocks and agency-related factors, thereby building a bridge between both perspectives.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research has already shown that many people experience shocks and that they impact their long-term career outcomes Scott & Hatalla, 1990;Williams et al, 1998), yet specific knowledge on whether and how the frequency of occurrence might impact career outcomes is less clear. For example, it would be interesting to examine whether experiencing multiple career shocks over time might diminish (negative shocks) or enhance (positive shocks) individuals' employability (Forrier et al, 2015), proactive career behaviours (De Vos et al, 2009) and the sustainability of their careers (De Vos & Van der Heijden, 2015). As such, we also call for research that examines the interplay between career shocks and agency-related factors, thereby building a bridge between both perspectives.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…For example, both social cognitive career theory (Lent et al, 1994) and career construction theory (Savickas, 2005) -two of the most frequently cited career theories in recent years -are premised on the notion of preparing for decision-making and acting upon those preparations via goaldirected behaviours. Empirical research has closely followed this trend, as evidenced by an emphasis on topics such as career self-management (King, 2004), proactive career behaviours (De Vos, De Clippeleer, & Dewilde, 2009), career crafting (Akkermans & Tims, 2017) and employability (Forrier, Verbruggen, & De Cuyper, 2015;Van der Heijde & Van der Heijden, 2006). Indeed, a recent review of papers published between 2012 and 2016 in four leading career journals showed that career decision-making, career mobility, career capital, employability and proactive career behaviours are among the most popular topics in the recent careers literature (Akkermans & Kubasch, 2017).…”
Section: Introductionmentioning
confidence: 96%
“…That is, because individuals themselves are nowadays primarily responsible for achieving career success, it is crucial that they master career‐related competencies that can help them navigate their career. Accordingly, recent research has shown that career competencies, which can be characterised as knowledge, skills, and abilities that affect career opportunities (Forrier, Sels, & Stynen, ), are important predictors of career success (De Vos, De Clippeleer, & Dewilde, ). For example, Kuijpers, Schyns, and Scheerens () demonstrated a positive association between career competencies and objective career success (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…One way of achieving this could be through the development of career competencies, defined as “knowledge, skills, and abilities central to career development, which can be influenced by the individual” (Akkermans, Brenninkmeijer, Huibers, & Blonk, ). In a recent study, Akkermans et al () reviewed the available literature on career competencies, thereby integrating the boundaryless career perspective (“three ways of knowing”; Eby et al, ), the protean career perspective (“career metacompetencies”; Briscoe & Hall, ), the career self‐management perspective (De Vos et al, ; King, ), and the human capital perspective (Kuijpers et al, ). Based on this integration of career perspectives, Akkermans et al () developed a career competency framework consisting of three dimensions: reflective career competencies, communicative career competencies, and behavioral career competencies.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the features of this new working context, the protean (Hall, 2004), the boundaryless (Arthur, 2014) and the sustainable (Van der Heijden y De Vos, 2015) career concepts have emerged as dominant topics in career research. Some scholars have introduced the career self-management perspective (De Vos et al, 20001), others the human capital perspective (Kuijpers et al, 2006) or the career adaptability (Nazar y Van der Heijden, 2014). Recently, based on meta-analytic correlations among components of protean and boundaryless career orientations, Kostal and Tiernik (2017) coined the term new career orientations to refer to the individual differences in such attitudes and preferences for protean and boundaryless careers.…”
Section: Introductionmentioning
confidence: 99%